Longitudinal effect following initiation of highly active antiretroviral therapy on plasma and cervico-vaginal HIV-1 RNA among women in Burkina Faso. Issue 3 (30th November 2007) - Nagot, N; Ouedraogo, A; Weiss, H A; Konate, I; Sanon, A; Defer, M-C; Sawadogo, A; Andonaba, J-B; Vallo, R; Becquart, P; Segondy, M; Mayaud, P; et al.
Abstract : Background: Highly active antiretroviral therapy (HAART) could decrease HIV-1 transmissibility by reducing genital and plasma HIV-1 RNA. Methods: We evaluated the effect of HAART on genital and plasma HIV-1 RNA in a cohort of 39 antiretroviral-naïve women in Burkina Faso. Cervico-vaginal lavages were collected before HAART initiation and at six visits over 28 weeks while on HAART. Blood samples were collected at baseline and at three and four visits for CD4 and plasma HIV-1 RNA measurements, respectively. Results: Before HAART, 72% of women had detectable genital HIV-1 RNA. After 18 weeks on HAART, only one woman (2.5%) had detectable plasma HIV-1 RNA and two women (5.1%) had detectable genital HIV-1 RNA. Similar results were observed at each follow-up visit. However, 16/34 (47%) women with consistently undetectable plasma HIV-1 RNA shed HIV-1 at least once between weeks 18 and 28. In samples with detectable genital HIV-1, the mean quantity of HIV-1 RNA decreased from 3.87 prior to HAART to 3.04 log10 copies/mL at last visit (median 29 weeks; a 6.8-fold decrease in absolute number of copies/mL) (p = 0.04). A significant median CD4 lymphocyte cell gain of 121 cells/μL (interquartile range 59 to 204) was measured between pre-HAART and last visit. Conclusion: These findings suggest that HAART could play a role in reducing HIV transmission in Africa; however, they underscore the need to emphasise safe sex practices with patients taking HAART.